2003
DOI: 10.1002/app.11966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different isocyanates on the properties of soy‐based polyurethanes

Abstract: New types of polyurethanes were prepared by reacting soybean oil-based polyol and different isocyanates. The polyurethanes can be used as foams, elastomers, coatings, adhesives, etc. Their properties strongly depend on crosslinking density and the structure of isocyanates. Aromatic triisocyanates impart the highest density, glass transition, modulus, and tensile strength, but have the lowest elongation at break, swelling in toluene, and impact resistance. Aliphatic triisocyanates and diisocyanates give rubbery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
129
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 100 publications
3
129
1
1
Order By: Relevance
“…%, atmospheric pressure, 110 °C), assumed that Tamami's results on the achievement of conversion of 94 % are wrong. The comparison of EG conversion data received by infrared spectroscopy method and a titrimetric method (100 and 78 % respectively) made the basis of such assumption and showed that the chemical method gives more precise results [7]. The data of physical-mechanical NIPU testing testify indirectly to a lower than 94 % conversion of EG for CC obtained by Tamami [7].…”
Section: Atmospheric Pressure Synthesismentioning
confidence: 95%
See 4 more Smart Citations
“…%, atmospheric pressure, 110 °C), assumed that Tamami's results on the achievement of conversion of 94 % are wrong. The comparison of EG conversion data received by infrared spectroscopy method and a titrimetric method (100 and 78 % respectively) made the basis of such assumption and showed that the chemical method gives more precise results [7]. The data of physical-mechanical NIPU testing testify indirectly to a lower than 94 % conversion of EG for CC obtained by Tamami [7].…”
Section: Atmospheric Pressure Synthesismentioning
confidence: 95%
“…The main part of researches is devoted to epoxidized soybean oil (ESBO) carbonation [6][7][8][9][10][11][12], in some works the epoxidized linseed oil (ELSO) [5,13] is used. Such choice is defined by the availability of these oils which are large-capacity products [14], they are widely applied at halogenated polymers processing (for example, polyvinylchloride).…”
Section: Main Partmentioning
confidence: 99%
See 3 more Smart Citations